Peran Dewan Pengawas Syariah (DPS) Dalam Pasar Modal Syariah di Indonesia - Erlania, Siti (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2023)
The development of the investment world in Indonesian society is increasing. One form of investment that is widely used is one of them investing in the Islamic Capital Market. One of the important elements in the implementation of sharia capital market activities is the role of the Dewan Pengawas Syariah (DPS) which has the main role to oversee sharia compliance. The method used in this paper is a descriptive research with a normative juridical approach. The roles and duties of DPS have been detailed in the regulations of the Financial Services Authority (OJK) as the regulator on the Islamic capital market. However, Indonesia should already have a special law dealing with the Islamic capital market because the development of the Islamic capital market has been so rapid and in demand by the public